2015
DOI: 10.3897/dez.62.5685
|View full text |Cite
|
Sign up to set email alerts
|

Larval muscle attachment site (MAS) patterns are a conserved character among Piophilini flies (Diptera, Piophilidae)

Abstract: The dorsoventral muscle attachment sites (MAS) patterns are described for six species of the tribe Piophilini (Diptera: Piophilidae): Centrophlebomyia furcata (Fabricius), Liopiophila varipes (Meigen), Piophila casei (Linnaeus), Piophila megastigmata McAlpine, Prochyliza nigrimana (Meigen) and Stearibia nigriceps (Meigen). Comparison between the MAS patterns of Piophilini and previous descriptions for Calliphoridae (Diptera) revealed differences in the muscle equipment between the larvae of both taxa. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Preliminary analyses of Piophilini species showed that their muscle equipment is clearly different from the Calliphoridae and Sarcophagidae ( Figure 7 ). The very similar species patterns observed between the two closely related Piophilina genera and a more distantly related genus of Thyreophorina, however, suggest that the larval MAS patterns may be highly conserved among the group [ 52 ]. Sufficiently conspicuous variations for reliable species differentiation were not visible to the naked eye.…”
Section: Approach From the Biological Perspectivementioning
confidence: 99%
“…Preliminary analyses of Piophilini species showed that their muscle equipment is clearly different from the Calliphoridae and Sarcophagidae ( Figure 7 ). The very similar species patterns observed between the two closely related Piophilina genera and a more distantly related genus of Thyreophorina, however, suggest that the larval MAS patterns may be highly conserved among the group [ 52 ]. Sufficiently conspicuous variations for reliable species differentiation were not visible to the naked eye.…”
Section: Approach From the Biological Perspectivementioning
confidence: 99%